FODDER CUTTER MACHINE INJURIES OF HAND - Shrestha, Kishor Man; Shrestha, Bipan; Kandel, Prakriti Raj; Baral, Rajiv; Pandey, Alok; Singh, Gyaneshwar Prasad (Journal of Universal College of Medical Sciences, 2018)
Introduction: Fodder cutter machine injuries of the hand are common accidents faced in agriculture sectors requiring a specialist and contributing to severe disability and morbidity which directly affect the functional capability of an individual. However studies on these injuries have not been conducted in this country (Nepal) so we conducted this study to identify epidemiological risk factors (age, sex, site of injury, day of injury and the severity of the injury) attending Universal College of Medical Sciences (UCMS-TH), Bhairahawa. Material and Methods: This is hospital based observational study conducted at UCMS-TH, Bhairahawa among the patients attending with hand injury caused by fodder cutting machine. The study period was from August 2011 to August 2013. Results: Fifty five patients (31.7%), out of 175 patients with hand injury attending the casualty department of the hospital were caused by fodder cutter machines. The injury was more common in children below 15 yrs with the mean age of 15.755 yrs (2-57 yrs) while playing in the field (72.7%). Out of that in 25.5% of cases the injury had occurred on Saturday being a weekly holiday in Nepal. In the present study, 60% of cases were males and 49.1 % of cases had fracture of bones with high incidence of injury of the right hand which was 52.7%. Most of the cases having fractures were of Gustilo II variety (51.8%) and 90% of cases were of minor to moderate grades of severity of hand injury on grading by HISS grading. Conclusion: In the present study, most of the injuries of hand were caused by fodder cutter machine that leads to the potential for serious handicap more commonly in the children below 15yrs. So, the efforts should be made by concern authorities for improving the knowledge for safe handling and production of safer agricultural machines to reduce the accidents as well as provision of standard but affordable healthcare for victims of the accidents to reduce the accidental disability. Journal of Universal College of Medical Sciences Vol. 6, No. 1, 2018, Page: 14-18